2022
DOI: 10.1155/2022/6439787
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition, Ignition Process and Combustion Behavior of Nitrate Ester Plasticized Polyether Propellant at 0.1–3.0 MPa

Abstract: Nitrate ester plasticized polyether (NEPE) propellant is widely used in solid rocket motors, having both good mechanical properties and high specific impulse. However, its ignition and combustion process are complex and need to be better understood. In this study, a high-pressure sealed combustion chamber was constructed, a thermogravimetry-differential scanning calorimetry was used to investigate the thermal decomposition process, and a high-speed camera was used to capture the ignition process and combustion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…In previous studies, it was found that the burning rate of propellant is one of the important factors influencing aluminum agglomeration [38]. Therefore, in this section's model, the influence of burning rate on agglomeration needs to be considered.…”
Section: The Establishment Of Al Agglomeration Modelmentioning
confidence: 99%
“…In previous studies, it was found that the burning rate of propellant is one of the important factors influencing aluminum agglomeration [38]. Therefore, in this section's model, the influence of burning rate on agglomeration needs to be considered.…”
Section: The Establishment Of Al Agglomeration Modelmentioning
confidence: 99%